Efficacy and safety of Danlou tablets in traditional Chinese medicine for coronary heart disease: a systematic review and meta-analysis - Mao, WeiLi; Lu, Peng; Wan, Renhong; Mao, Kaili; Lv, Yanzhu; Hu, Jie; Fu, Zhenling; Wang, Jun (Frontiers in Cardiovascular Medicine, 2023)
Background Danlou tablets exert auxiliary advantages in treating coronary heart disease (CHD), but a summary of evidence-based proof is lacking. This study aims to systematically evaluate Danlou tablets in treating CHD from two aspects, including efficacy and safety. Methods By a thorough retrieval of the four English databases, namely, PubMed, The Cochrane Library, Embase, and Web of Science, and the four Chinese databases, namely, CNKI, Wanfang, VIP database, and China Biomedical Literature Service System, we found all randomized controlled trials (RCTs) related to Danlou tablets in treating CHD. The retrieval time was from the construction of the database to April 2022. We engaged two researchers to screen the studies, extract the required data, and assess the risk of bias. We then used RevMan5.3 and STATA.14 software to conduct a meta-analysis. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to evaluate the quality of outcome indicators. Results Seventeen RCTs involving 1,588 patients were included. The meta-analysis results are displayed as follows: clinical treatment effect [risk ratio (RR) = 1.22, 95% confidence interval (CI): 1.16, 1.28, P < 0.00001], angina pectoris duration [MD = −0.2.15, 95% CI: −2.91, −1.04, P < 0.00001], angina pectoris frequency [standard mean difference (SMD) = −2.48, 95% CI: −3.42, −1.54, P < 0.00001], angina pectoris degree [SMD = −0.96, 95% CI: −1.39, −0.53, P < 0.0001], TC [MD = −0.71, 95% CI: −0.92, −0.51, P < 0.00001], TG [MD = −0.38, 95% CI: −0.53, −0.22, P < 0.00001], low-density lipoprotein cholesterol [MD = −0.64, 95% CI: −0.76, −0.51, P < 0.00001], high-density lipoprotein cholesterol [MD = 0.16, 95% CI: 0.11, 0.21, P < 0.00001], and adverse events [RR = 0.46, 95% CI: 0.24, 0.88, P = 0.02]. Conclusion The current evidence suggests that the combination of Danlou tablets and Western medicine can enhance the efficacy of CHD and does not increase adverse events. However, because of the limited number and quality of the included studies, the results of our study should be treated with caution. Further large-scale RCTs are necessary to verify the benefits of this approach.